Strong compact properties of the mappings and K-Radon-Nikodym property - Stonyakin, F. S.; Orlov, I. V. (Methods of Functional Analysis and Topology, 2010)
For mappings acting from an interval into a locally convex space, we study properties of strong compact variation and strong compact absolute continuity connected with an expansion of the space into subspaces generated by the compact sets. A description of strong K-absolutely continuous mappings in terms of indefinite Bochner integral is obtained. A special class of the spaces having K-Radon-Nikodym property is obtained. A relation between the K-Radon-Nikodym property and the classical Radon-Nikodym property is considered.